2005
DOI: 10.3354/meps301185
|View full text |Cite
|
Sign up to set email alerts
|

Growth and reproduction of gelatinous zooplankton exposed to low dissolved oxygen

Abstract: The lobate ctenophore Mnemiopsis leidyi and the scyphomedusan jellyfish Chrysaora quinquecirrha are seasonally important consumers in the food web of Western Atlantic and Gulf of Mexico estuaries, including Chesapeake Bay. The abundance and importance of these gelatinous species may be increasing as a result of anthropogenic alteration of these systems, particularly the increasing severity and extent of low dissolved oxygen. Ctenophores and jellyfish are more tolerant of hypoxia than co-occurring finfish, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…In ctenophores, Grove and Breitburg (2005) found a significant reduction in growth at DO levels of 1.1 and 1.8 mL O 2 L −1 , both in small (0.2 to 2.0 mL biovolume) and larger (8.0 to 17.6 mL biovolume) specimens. This phenomenon seems to occur especially at high prey densities.…”
Section: Gelatinous Planktonmentioning
confidence: 97%
See 1 more Smart Citation
“…In ctenophores, Grove and Breitburg (2005) found a significant reduction in growth at DO levels of 1.1 and 1.8 mL O 2 L −1 , both in small (0.2 to 2.0 mL biovolume) and larger (8.0 to 17.6 mL biovolume) specimens. This phenomenon seems to occur especially at high prey densities.…”
Section: Gelatinous Planktonmentioning
confidence: 97%
“…It is argued that because of their higher tolerance against low oxygen (than e.g. finfish; Grove and Breitburg, 2005) they are predestined to take a dominant role in ecosystems with declining oxygen conditions. In particular, ctenophores seem to exhibit a high degree of predation pressure on copepods (Purcell and Decker, 2005).…”
Section: Gelatinous Planktonmentioning
confidence: 99%
“…Ritter & Montagna (1999) also observed that polychates and oligochaetes tolerated hypoxic conditions better than other benthic species in a Texas Bay. In other words, hypoxia affects the population prosperity of living organisms differently according to taxon (Breitburg et al 1999, Keister et al 2000, Decker et al 2004, Grove & Breitburg 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning A. aurita, a recent study has shown that the medusae were more tolerable to low DO conditions (Ϲ4 mg O 2 L Ϫ1 ; equal to 2.8 ml O 2 L Ϫ1 ) than Spanish mackerel, and the number of fish larvae consumed by medusae increased with decreasing DO concentrations (Shoji et al 2005). Thus the effects of low DO concentrations may dramatically impact trophic interactions in the water column (Breitburg et al 1999, Keister et al 2000, Decker et al 2004, Grove & Breitburg 2005.…”
Section: Introductionmentioning
confidence: 99%
“…At approximately 0900 the following morning, adult ctenophores were removed and lengths and volumes recorded. Water from each jar was strained through a 35 m sieve, preserved with 10% acid Lugol's solution (Sullivan and Gifford, unpublished data;Grove and Breitburg, 2005), and eggs were enumerated. Egg production was normalized by ctenophore volume to facilitate comparisons among individuals.…”
Section: Methodsmentioning
confidence: 99%